PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN SIKAP KERJASAMA PESERTA DIDIK KELAS V PADA PEMBELAJARAN IPA - Wulandari; Ferina Agustini; Sukamto; Sri Mariyatun (STKIP Subang, 2023)
The purpose of this study was to test whether applying the Problem-Based Learning model could improve students' cooperation in learning science in grade V SDN Sampangan on the topic of food chains. This research is a type of classroom action research with the subject of 27 class V students at SDN Sampangan 02 Semarang in the odd semester of the 2022/2023 academic year. The method used is a classroom action research design which consists of four stages: planning, implementing, observing, and reflecting. This research was planned to be conducted in two cycles with planning stages which included scheduling action meetings, preparing lesson plans based on the PBL model, making teaching aids, compiling formative tests, and student collaboration observation sheets. After the planning stage, there will be two meetings in each cycle, with observations made on the observation sheet of student cooperation that has been prepared previously. The results of the observations will be used to reflect and determine the continuation of the action cycle. Based on the results of observations on the implementation of cycles I and II, there was an increase in students showing indicators of always communicating, from 8 students in cycle 1 to 11 students in cycle 2.